Assessment of Single-Word Production for Children under Three Years of Age: Comparison of Children with and without Cleft Palate. (30th April 2012) - Scherer, Nancy J.; Williams, Lynn; Stoel-Gammon, Carol; Kaiser, Ann
Abstract : Background . This study reports comparative phonological assessment results for children with cleft lip and/or palate (CLP) to typically developing peers using an evaluation tool for early phonological skills. Methods . Children without clefts (NC = noncleft) and 24 children with CLP, ages of 18–36 months, were evaluated using the Profile of Early Expressive Phonological Skills (PEEPSs) [1]. Children interacted with toy manipulatives to elicit a representative sample of target English consonants and syllable structures that are typically acquired by children between 18 and 27 months of age. Results . Results revealed significant differences between the two groups with regard to measures of consonant inventory, place of articulation, manner of production, accuracy, and error patterns. Syllable structure did not indicate differences, with the exception of initial consonant clusters. Conclusions . findings provide support for PEEPS as a viable option for single-word assessment of children with CLP prior to 3 years of age.